Sex‐specific daily spawning seaward migration of striped mullet Mugil cephalus in a coastal lagoon - G. Katselis; K. Koukou; A. Ramfos; D. K. Moutopoulos (Journal of Fish Biology, 2015)
The sex‐specific daily spawning seaward migration of striped mullet Mugil cephalus was analysed in Palaiopotamos Lagoon (western Greek coast, eastern Mediterranean Sea) in an 86 day time series. The data set included the daily number of M. cephalus catches in barrier traps, as well as a time series of some weather variables. The analysis revealed an important linkage of the daily migration rate as well as a sex‐specific response of the species to the lunar cycle and the short‐term fluctuation of weather variables. The daily migration pattern of females was more persistent than that of males, indicating a possible female leadership role during the spawning migration. Multiregression models described quite accurately the sex‐specific daily migration rates of the species, thus providing a potentially powerful tool regarding the lagoon fishery management of M. cephalus , especially in the context of climate change.